HUBUNGAN EFIKASI DIRI DENGAN KEMAMPUAN PERENCANAAN KARIR PESERTA DIDIK KELAS XI MA CAHAYA INSANI AL UM - Rizki Nur Fitriani; Putri Ria Angelina; Fahmi Irfani (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
One of the developmental tasks of high school students is readiness to organize their future as their role as adults. Therefore, careful career planning is needed so that students can plan their careers according to the students' strengths, weaknesses and abilities. One of the factors that can influence thorough career planning is belief in one's own abilities or what is called self-efficacy. This research aims to determine the relationship between self-efficacy in class XI students at MA Cahaya Insani Al UM. The hypothesis proposed in this research is that there is a positive relationship between self-efficacy and career planning abilities. The subjects in this research were 34 MA Cahaya Insani Al Um students. The sampling technique used is non-probability sampling technique. (Saturated Sampling). Research data was collected using two scales, namely the self-efficacy scale and the career planning ability scale. Data collection techniques use primary data and secondary data. The results of the research show that there is a positive relationship between self-efficacy and career planning abilities as indicated by a significance result of 0.606. This shows that there is a very significant positive relationship between self-efficacy and the career planning abilities of class XI students at MA Cahaya Insani Al Um.